Economic Recovery Strategy in the Tourism Sector in the New Normal Era of DKI Jakarta - Alivia Rachmawati (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2022)
"The strategy for Indonesia's economic recovery in the tourism sector in DKI Jakarta in the new era is common." The impact of the Covid-19 pandemic was in the form of a drastic decrease in tourist arrivals in the tourism sector and the Indonesian economy in decline. Therefore, an economic recovery strategy is needed so that there is an economic response after the pandemic. The new policy resulted in limited community mobility. A decrease in economic activity which causes a decrease in income. The method used in this research is qualitative method. This research technique uses the Research Library technique to collect various information and data in depth through literature, books, notes, journals, and other sources. The efforts to restore the tourism economy in DKI Jakarta have encouraged the confidence of stakeholders, including tourism industry players, that the DKI Jakarta Provincial Government is committed to continuing the process. One of the developments after the Covid-19 outbreak is tourism development so that it can encourage stakeholders. These interests are to synergize according to their respective abilities, including reinvesting business entities in the tourism economy in DKI Jakarta. Tourism recovery planning that involves optimizing the roles of two main tourism sectors, namely the DKI Jakarta Government as the public authority with the authority for tourism recovery policies and economic actors as the organizer of tourism activities. Externally, the DKI Jakarta Provincial Government needs to communicate and coordinate with tourism industry players, formulating tourism economic policy instruments after the Covid-19 recovery, namely participatory, collaborative and synergistic.